Perspectives in developmental change - Gallaher, Art, 1925- (University of Kentucky Press, 1968)
In this volume a number of distinguished social scientists representing the disciplines of anthropology, sociology, psychology, economics, and political science, explore essential problems of developmental change against the theoretical background and empirical data of their own and related disciplines. Developmental change is here viewed under a broad perspective. The considerations range from the problems that arise when human beings are confronted by change, to investment planning and decision-making in a specific case against a background of general poverty and a high birthrate, to the prob.